The Pathway of Female Couples in a Fertility Clinic - Pedro Brandão; Nathan Ceschin; Victor Hugo Gómez (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective The present study aims to describe the main characteristics of female couples resorting to a fertility clinic, to understand whether these patients have clear previous plans concerning procreation and how they end up completing their family planning, and to briefly describe the main outcomes of the recepción de ovocitos de pareja (ROPA, in the Spanish acronym: in English, reception of partner's oocytes) method. Methods This is a descriptive retrospective study of the pathway and outcomes of female couples in a fertility clinic during a 2-year period. Results A total of 129 couples were treated. Only one third of the couples had no condition potentially affecting fertility or advanced age. Most couples were decided to undergo artificial insemination or in vitro fertilization and the majority kept their plans, as opposed to 38% of the couples who decided to the ROPA method (lesbian shared in vitro fertilization) who changed plans. Live birth rates per treatment (including frozen embryo transfers) for artificial insemination, 58% for in vitro fertilization, 80% for treatments with donated oocytes or embryos, and 79% for ROPA. Four in five couples achieved live births. Conclusion The present study highlights the importance of a thorough medical workup in same-sex couples resorting to assisted reproduction. Despite the higher-than-expected rates of fertility disorders, the outcomes were good. Most couples end up in a single parented method. Furthermore, the results of the ROPA method are reassuring.